2017
DOI: 10.14569/ijacsa.2017.080423
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Breast Cancer Diagnosis Scheme based on Two-Step-SVM Technique

Abstract: Abstract-This paper proposes an automatic diagnostic method for breast tumour disease using hybrid Support Vector Machine (SVM) and the Two-Step Clustering Technique. The hybrid technique is aimed at improving the diagnostic accuracy and reducing diagnostic miss-classification, thereby solving the classification problems related to Breast Tumour. To distinguish the hidden patterns of the malignant and benign tumours, the Two-Step algorithm and SVM have been combined and employed to differentiate the incoming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Yue et al examined machine learning (ML) techniques used for the diagnosis and prognostics of breast cancer [20]. The researchers based their study on studies with the aid of SVM [21], NN [22], KNN [23], [24], and DT algorithms [25]. In addition, the breast cancer list from Wisconsin was used.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Yue et al examined machine learning (ML) techniques used for the diagnosis and prognostics of breast cancer [20]. The researchers based their study on studies with the aid of SVM [21], NN [22], KNN [23], [24], and DT algorithms [25]. In addition, the breast cancer list from Wisconsin was used.…”
Section: Related Workmentioning
confidence: 99%
“…The alternative nitrate networks is the best so that the accuracy of the prediction by 97.4% [30]. Osman [21] proposed automatic breast cancer diagnostic approach using two-step clustering method and support vector machine algorithm. The hybrid approach aims to improve diagnosis precision and the medical misdiagnosis identification, thus solving breast-tumor-related screening problems.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, when cancer spreads to healthy regions, it's called distant metastasis. Because of their similarities, locoregional recurrence (LLR) is a diagnostic term that may be used to characterize both local and regional recurrence [4]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, by employing data mining techniques and data modeling, cancer patients with dangerous INTRODUCTION conditions might be diagnosed [2]. For example, in recent studies, the precision and accuracy of sequential minimal optimization (SMO) and SVM algorithms in diagnosing breast cancer were evaluated [4][5][6][7][8]. The studies indicated that the SVM and SMO algorithms were superior to other algorithms in increasing the precision level of diagnosis.…”
mentioning
confidence: 99%